Improving access to school health services as perceived by school professionals - Janine Bezem; Debbie Heinen; Ria Reis; Simone E. Buitendijk; Mattijs E. Numans; Paul L. Kocken (BMC, 2017)
Abstract Background The organisation of health assessments by preventive health services focusing on children's health and educational performance needs to be improved due to evolving health priorities such as mental health problems, reduced budgets and shortages of physicians and nurses. We studied the impact on the school professionals' perception of access to school health services (SHS) when a triage approach was used for population-based health assessments in primary schools. The triage approach involves pre-assessments by SHS assistants, with only those children in need of follow-up being assessed by a physician or nurse. The triage approach was compared with the usual approach in which all children are assessed by physicians and nurses. Methods We conducted a cross-sectional study, comparing school professionals' perceptions of the triage and the usual approach to SHS. The randomly selected school professionals completed digital questionnaires about contact frequency, the approachability of SHS and the appropriateness of support from SHS. School care coordinators and teachers were invited to participate in the study, resulting in a response of 444 (35.7%) professionals from schools working with the triage approach and 320 (44.6%) professionals working with the usual approach. Results Respondents from schools using the triage approach had more contacts with SHS and were more satisfied with the appropriateness of support from SHS than respondents in the approach-as-usual group. No significant differences were found between the two groups in terms of the perceived approachability of SHS. Conclusions School professionals were more positive about access to SHS when a triage approach to routine assessments was in place than when the usual approach was used. Countries with similar population-based SHS systems could benefit from a triage approach which gives physicians and nurses more opportunities to attend schools for consultations and assessments of children on demand.